2021
DOI: 10.1038/s41598-021-91373-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling analysis of muscle tissue reveals potential candidate genes affecting water holding capacity in Chinese Simmental beef cattle

Abstract: Water holding capacity (WHC) is an important sensory attribute that greatly influences meat quality. However, the molecular mechanism that regulates the beef WHC remains to be elucidated. In this study, the longissimus dorsi (LD) muscles of 49 Chinese Simmental beef cattle were measured for meat quality traits and subjected to RNA sequencing. WHC had significant correlation with 35 kg water loss (r = − 0.99, p < 0.01) and IMF content (r = 0.31, p < 0.05), but not with SF (r = − 0.20, p = 0.18) and pH (r … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…Buffaloes that received green feed showed changes in the expression of many genes encoding factors associated with muscle structure and function. Of particular interest is the increased expression of KCNK10, CACNG4, and ATP2B4 genes, encoding factors that modulate the homeostasis of Ca 2+ [77][78][79][80], a second messenger important for muscle contraction and differentiation, which allows to suppose that green feed might stimulate the ruminal muscular function. Furthermore, green feed modulated, with a different direction, genes encoding structural components of the cytoskeleton, such as MYH11, DES, and LOC102397197 (or TUBA1D), and factors promoting its assembling, such as TPPP, TPPP3, thus suggesting an impact of this diet on muscular structure.…”
Section: Discussionmentioning
confidence: 99%
“…Buffaloes that received green feed showed changes in the expression of many genes encoding factors associated with muscle structure and function. Of particular interest is the increased expression of KCNK10, CACNG4, and ATP2B4 genes, encoding factors that modulate the homeostasis of Ca 2+ [77][78][79][80], a second messenger important for muscle contraction and differentiation, which allows to suppose that green feed might stimulate the ruminal muscular function. Furthermore, green feed modulated, with a different direction, genes encoding structural components of the cytoskeleton, such as MYH11, DES, and LOC102397197 (or TUBA1D), and factors promoting its assembling, such as TPPP, TPPP3, thus suggesting an impact of this diet on muscular structure.…”
Section: Discussionmentioning
confidence: 99%
“…One of the interesting genes was the ANK1 which was found to have a link between polymorphism in its promoter region and the meat quality of porcine 37 and cattle 38 , 39 . Additionally, the HSPA13 gene influences meat quality by affecting the water holding capacity of meat 40 . The results of some studies 41 , 42 have indicated an association between the ANKS1B gene and growth plus body size in sheep.…”
Section: Discussionmentioning
confidence: 99%